Real-time detection of carboplatin using a microfluidic system. Issue 22 (5th September 2016) - Phairatana, Tonghathai; Leong, Chi Leng; Gowers, Sally A. N.; Patel, Bhavik Anil; Boutelle, Martyn G.
Abstract : A novel on-line microfluidic assay for the chemotherapy agent carboplatin will allow sensitive detection of the drug directly applied to the tumour as it emerges from the tumour into healthy tissue. Abstract : A microfluidic sensor system based on a carbon nanotube-epoxy composite electrode was fabricated to allow detection of the presence of the anti-cancer drug carboplatin in healthy tissue in real time during chemotherapy. Detection of carboplatin was carried out by observing the effects of the drug on the differential pulse voltammetry of free purine bases using a novel carbon nanotube-epoxy composite electrode. In free solution these electrodes performed better than glassy carbon electrodes for oxidation of the free purine bases AMP and GMP, and than DNA-modified carbon nanotube-epoxy composite sensors for detection of carboplatin. On-line carboplatin detection was performed using a computer-controlled microfluidic platform. The methodology for on-line carboplatin detection was optimised in terms of the analysis time and to allow repeated carboplatin measurement using the same electrode. Microdialysis sampling and our microfluidic platform were combined to give a proof-of-concept system for real-time carboplatin detection with a limit of detection of 0.014 μM carboplatin in the sampled media. This paper is dedicated to Craig Lunte's pioneering work in analysis and microdialysis.